ABOUT ECHINOCOCCOSIS OF ANIMALS IN UZBEKISTAN - Achilov Tursunmurod N.; Aminjonov Sherzod M. (Bright Mind Publishing, 2025)
This article presents the work of scientists in the field of parasitology, especially about the disease of echinococcosis of its development, as well as about the taxonomy of the parasite.
Keywords: Echinococcosis, unoccupied, stopped, intermediate host, bubble, parasite.